Stereotactic Radiosurgery and Stereotactic Radiotherapy for Brain Metastasis: Experience from a Tertiary Cancer Centre - EK, Nabeel Yahiya; Francis, Anitta; NV, Vinin; S, Chythra; M, Geetha; Jones, Joneetha (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Brain metastases are a common and serious complication in cancer patients, significantly impacting neurological function and quality of life. Stereotactic radiosurgery (SRS) and fractionated stereotactic radiotherapy (FSRT) offer focal, precise treatment options with potentially lower toxicity compared to whole brain radiotherapy. This study aims to evaluate the clinical outcomes and dosimetric parameters of SRS and FSRT in patients with brain metastases treated at a tertiary cancer center. Materials and Methods: A retrospective observational study was conducted on 13 patients with solitary brain metastases treated with SRS or FSRT from 2014 to 2022. Patient data, treatment details, and dosimetric parameters were collected. Overall survival (OS) and local progression-free survival (LPFS) were estimated using the Kaplan–Meier method. Results: The median age of patients was 56 years, with lung (62%) and breast (38%) as the most common primary tumors. The median OS was 12 months, with 1- and 2-year OS rates of 48% and 29%, respectively. LPFS at 1 and 2 years was 47% and 19%. Dosimetric parameters, including target volumes and plan quality indices, adhered to established stereotactic radiotherapy standards. No symptomatic radionecrosis was reported. Systemic therapy use was limited due to resource constraints. Conclusion: SRS and FSRT can be delivered with high dosimetric precision and acceptable toxicity in patients with brain metastases, even in settings with limited access to advanced systemic therapies. These findings support the continued use of focal radiotherapy modalities and underscore the need for larger prospective studies incorporating modern systemic treatments to optimize management and outcomes.